Evolution of the SYNTAX score (I, II and II 2020): development, application and limitations in everyday clinical practice - Orlic, Dejan; Zobenica, Vladimir; Tesic, Milorad; Juricic, Stefan; Zivkovic, Milorad; Ristic, Marko; Beleslin, Branko; Aleksandric, Srdjan (Medical Research, 2026)
Surgical myocardial revascularization is the gold standard for myocardial revascularization in chronic coronary syndrome (CCS). The first randomized trials comparing bare metal stent (BMS) implantation and aorto-coronary bypass graft surgery (CABG) resulted in similar mortality and myocardial infarction rate, and lower rate of repeat revascularization after CABG compared to BMS implantation, directed the development of drug eluting stents (DES) with the lower rate of clinical restenoses. Over the years, there was a need for objective assessment and calculation of risk and benefit of both surgical and percutaneous myocardial revascularization, and giving an advantage to one of these two methods, or equipoise for a specific patient. SYNTAX score I was used for the quantitative assessment of coronary stenoses complexity in a patient with CCS. However, two major flaws of the SYNTAX score I, (1) absence of the assessment of functional significance of coronary stenosis, and (2) absence of clinical variables that may influence perioperative mortality rate, were partially overcome with development of SYNTAX score II including clinical variables that showed the greatest association with mortality (age, creatinine clearance, left ventricular ejection fraction, unprotected left main coronary artery disease, female gender, peripheral vascular disease and chronic obstructive pulmonary disease) and SYNTAX score II 2020 predicting 10-year mortality rate. The SYNTAX score II and II 2020 potentially can change the recommendation for myocardial revascularization based on SYNTAX score I alone. This review focuses on development of these scores, their accuracy, predicitve value and limitations in practical applications in an individual patient with CCS.
Keywords: SYNTAX scores, myocardial revascularization, prognosis